C12orf59 Promotes Esophageal Squamous Cell Carcinoma Progression via YAP-Mediated Epithelial-Mesenchymal Transition - Xu, Chunhua; Lin, Shan; Lu, Yanxin; Mao, Longyi; Li, Shi; Li, Zesong (Frontiers in Oncology, 2022)
C12orf59 is a novel gene widely expressed in diverse normal human tissues. Aberrant expression of C12orf59, which is involved in tumor progression, has been reported in a few types of cancer. However, its expression and biological function in esophageal squamous cell carcinoma (ESCC) remain largely unclear. Here, we found that the mRNA and protein levels of C12orf59 were prominently higher in both tumor tissues and most ESCC cell lines. Functionally, C12orf59 overexpression promoted ESCC cell proliferation, migration and invasion, whereas C12orf59 depletion worked oppositely. Mechanistically, C12orf59 exerted its oncogenic function through the induction of epithelial-mesenchymal transition (EMT) of ESCC cells, which relied on Yes-associated protein (YAP) dephosphorylation and nuclear translocation. Constitutively active YAP further facilitated cell migration, invasion and EMT induced by enforced C12orf59 overexpression. On the contrary, increased cell motility and EMT caused by enforced C12orf59 overexpression were dramatically repressed upon YAP inactivation by verteporfin. Thus, we conclude that YAP activation driven by C12orf59 contributes to the malignancy of ESCC through EMT and that targeting drugs for C12orf59 combined with YAP inhibitor may be a potential therapeutic strategy for ESCC.